Dielectric and piezoelectric properties near the morphotropic phase boundary for 0.94BNT-0.06BT ceramics synthesized by the solid-state combustion technique - Bhoowadol Thatawong; Pamornnarumol Bhupaijit; Yanwarood Lamyai; Naratip Vittayakorn; Theerachai Bongkarn (Ferroelectrics, 2022)
Ceramics of 0.94Bi0.5Na0.5TiO3-0.06BaTiO3 (0.94BNT-0.06BT) were synthesized by the solid-state combustion technique with various calcination and sintering temperatures (600-800 °C and 1100-1200 °C). A pure perovskite phase was obtained from the powder calcined at 750 °C for 2 h. The phase structure, microstructure, dielectric, ferroelectric and piezoelectric properties of the 0.94BNT-0.06BT ceramics were investigated. The XRD patterns showed coexisting phases of rhombohedral (R) and tetragonal (T) in all samples. Moreover, a good R:T phase ratio of 53:47, as found by Rietveld refinement, good grain growth and high density (5.84 g/cm3) were found with a sintering temperature of 1150 °C for 2 h. An excellent maximum dielectric constant (εm = 8405), good ferroelectric properties (Pr = 28.2 µC/cm2 and Ec = 22.1 kV/cm) and a high piezoelectric coefficient (161 pC/N) were observed in this sample, which was near a morphotropic phase boundary (MPB).
Keywords: Ferroelectric and Piezoelectric Materials; Microwave Dielectric Ceramics Synthesis; Multiferroics and related materials